Enhancing Culinary Business Financial Management For Rural Community Using Website-Based Cogs Calculator - Alexandra, Yoanita; Kristiyanti, Dinar Ajeng; Situmorang, Ringkar (JUAN (Jurnal Ultima Abdimas Nusantara), 2025)
The study focuses on the implementation of ecotourism programs to develop village tourism potential, with a specific emphasis on improving the financial management of culinary businesses. The activities involved increasing promotion and marketing of tourism destinations, developing skills and knowledge in tourism management, and providing training in financial record-keeping for micro, small, and medium-sized enterprises (MSMEs). The paper discusses the process and implementation methods of the community service activities, along with the significant benefits they provided for the rural community. The findings show that many of the MSMEs were not formally doing their financial record, resulting low and minus profit margin for some products. Through the results from COGS calculator, it is then suggested for MSME to reevaluate their cost of product and profit margin. The result contribute to the understanding of how community outreach initiatives can effectively support the financial management of culinary businesses in rural areas, ultimately fostering sustainable economic development.